The space social construction of the places: a look from the turn special - Araya Ramírez, Iliana (Revista Geográfica de América Central., 2018)
The objective of this essay is to relate the contributions of spatial turn and urban spatiality in the socio-spatial construction of places. The traditional conceptualization of space refers to the positivist conception of abstract space, which is transformed in the context of globalization that is accompanied by an epistemological transition. This is where the "spatial turn" proposes a new interpretation of urban spatiality from an interdisciplinary perspective that integrates the material and immaterial dimensions of space and the ways in which they become places. The construction of the place is elaborated from socio-spatial practices and spatial subjectivity; the first refers to the ways of inhabiting the city according to daily activities and the second is understood in social terms and the feelings towards the environment in dialogue between the place and the social actors.